2021
DOI: 10.1186/s12913-021-06645-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of audit and feedback to support change behaviour in healthcare organisations - a cross-sectional qualitative study of primary care centre managers

Abstract: Background This article addresses the role of audit and feedback (A&F) to support change behaviour and quality improvement work in healthcare organisations. It contributes to the sparse literature on primary care centre (PCC) managers´ views on A&F practices, taking into account the broad scope of primary care. The purpose was to explore if and how different types of A&F support change behaviour by influencing different forms of motivation and learning, and what contextual facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…Allgemein haben die theoretische Untermauerung der Qualitätsrückmeldung und darauf aufbauend die Berücksichtigung derjenigen Faktoren, die die Wirkung von Rückmeldungen zu medizinischen Leistungsdaten beeinflussen, in Deutschland bisher wenig Beachtung gefunden. Zu nennen sind vor allem die Fähigkeit der Adressaten, die Daten zu interpretieren und in Verbesserungen umzusetzen, deren Meinung zur Glaubwürdigkeit der Daten, deren Motivation, die Art der Rückkopplung und Kontextfaktoren wie die Qualitätskultur des jeweiligen Krankenhauses [ 35 , 36 ].…”
Section: Diskussionunclassified
“…Allgemein haben die theoretische Untermauerung der Qualitätsrückmeldung und darauf aufbauend die Berücksichtigung derjenigen Faktoren, die die Wirkung von Rückmeldungen zu medizinischen Leistungsdaten beeinflussen, in Deutschland bisher wenig Beachtung gefunden. Zu nennen sind vor allem die Fähigkeit der Adressaten, die Daten zu interpretieren und in Verbesserungen umzusetzen, deren Meinung zur Glaubwürdigkeit der Daten, deren Motivation, die Art der Rückkopplung und Kontextfaktoren wie die Qualitätskultur des jeweiligen Krankenhauses [ 35 , 36 ].…”
Section: Diskussionunclassified
“…Research has shown that audit and feedback generally leads to small but potentially important improvements within healthcare (Ivers et al, 2012). Further, research has shown that external audit and feedback can increase the "knowwhat" and "know-why" types of knowledge which may impact behavioural changes among healthcare providers (Glenngård & Anell, 2021). This is the kind of knowledge that is related to the culture-cognitive pillar.…”
Section: -Not Strong Enough Financial Incentives For Research To Improve Gamentioning
confidence: 99%
“…Our study is dedicated to identifying the mix of factors that are associated with an improvement of health professionals’ job satisfaction related to unit, organization, and regional government in the context of a series of large-scale surveys. Investigating employees’ satisfaction and perception about organizational climate with different governance levels seems essential in light of extant evidence showing the interconnection as well as the uniqueness of each governance layer in enhancing or threatening motivation and satisfaction across public administration fields, including government [ 12 , 13 ] and healthcare [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%